The morphology, phylogeny, and distribution of the pine-associated sequestrate fungus Lactarius cinnabarinus comb. nov. (= Zelleromyces cinnabarinus) in the United States, Argentina and Brazil - Alex Ernesto Somrau; Benjamin Lemmond; Natalia Andrea Ramirez; Orlando Fabián Poppof; Andrea Michling; Alexandre Gonçalves dos Santos Silva-Filho; Matthew Smith; Nicolás Niveiro (Plant and Fungal Systematics)
The sequestrate fungus Zelleromyces cinnabarinus was originally found beneath pines and was described from Louisiana, USA. Here we re-evaluate the morphology, taxonomy, and distribution of this species based on new specimens across the native range in the southeastern United States (USA), as well as introduced populations in Argentina and Brazil. Internal Transcribed Spacer (ITS) sequences of fungarium specimens indicate that this species is widespread in the southeastern USA with native pines and has been introduced to South America in cultivated pine plantations. An environmental sequence from ectomycorrhizal Pinus roots also confirms the symbiotic association with pines. Our data also indicate that Lactarius taedae , a sequestrate fungus recently described from Brazil, is a later synonym of Zelleromyces cinnabarinus . Lastly, our phylogenetic analysis of ITS sequences suggests that Zelleromyces cinnabarinus is nested within the genus Lactarius , so we recombine this sequestrate species as Lactarius cinnabarinus comb. nov.